(untitled) (Medical Forum Monthly, 2022)
Objective: To observe the association between the officers' dietary behavior and psychological distress during the pandemic. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted Department of Community Health Sciences Bahria University Medical and Dental College, Karachi at the June 2020 to July 2020. Materials and Methods: The convenience sampling was used to collect data. A Chi-square test and bivariate Pearson correlation were conducted, and SPSS version 23 was used to analyze the data. Results: A total of 161 house officers participated in the study, of which, most (73.9%) house officers were females, with a mean age of 24.7± 2.2 years. An association between the officers’ junk food consumption and psychological distress was found to be statistically significant, p < 0.05. Similarly, a significant positive correlation was observed between dietary behavior and distress, p < 0.05. Conclusion: COVID-19 pandemic has increased the burden on healthcare professionals globally and to cope with the situation the house officers are resorting to harmful behaviors such as consuming an unhealthy diet in Karachi. If not addressed, these behaviors will last and deteriorate their overall health and wellbeing in the long run.